2011
DOI: 10.1021/jp2043587
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Nanostructures of Cr2Te4O11and Mn2TeO6through Room-Temperature Chemical Transformations of Tellurium Nanowires

Abstract: Tubular ternary nanostructures of tellurium were made through chemical transformations of tellurium nanowires (Te NWs). These transformations occur through reactions with CrO3 and KMnO4, two of the strongest oxidizing agents. In the case of CrO3, the 1D structure of the NWs remained intact and the morphology changed to hollow wires of Cr2Te4O11, but reaction with KMnO4 resulted in the loss of 1D structure, forming a carbon onion-like object composed of Mn2TeO6. As the reaction proceeded, the crystallinity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Te NWs are semiconducting, known to show luminescence depending upon the aspect ratio of the NWs [24]. The as grown Te NWs show an emission maxima at 394 nm when excited at 352 nm.…”
Section: Photoluminescence Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Te NWs are semiconducting, known to show luminescence depending upon the aspect ratio of the NWs [24]. The as grown Te NWs show an emission maxima at 394 nm when excited at 352 nm.…”
Section: Photoluminescence Measurementsmentioning
confidence: 99%
“…The reactivity of tellurium nanowires (Te NWs) with thiol-containing molecules has also been studied [23] and it was reported that there was a redox reaction between TeO 2 , present on the NW surface, and thiols added into the solution that resulted in the reduction of TeO 2 to Te (0) with simultaneous oxidation of thiols to disulfides. These studies and studies such as the formation mechanism of Tubular Nanostructures of Cr 2 Te 4 O 11 and Mn 2 TeO 6 through room temperature chemical transformations of Te NWs indicated the combined effect of both redox reactions and nanoscale Kirkendall effect (NKE) in its formation [24]. As An example for the biocompatibility of NWs, Tellurium Platinate Nanowires has recently been used for Photothermal therapy of Cancer cells [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation